The effects of stress on brain and adrenal stem cells - de Celis, Maria F. Rubin; Bornstein, Stefan R.; Androutsellis-Theotokis, Andreas; Andoniadou, Cynthia L.; Licinio, J.; Wong, M.-L.; Ehrhart-Bornstein, M. (Nature Publishing Group, 2016)
The brain and adrenal are critical control centers that maintain body homeostasis under basal and stress conditions, and orchestrate the body’s response to stress. It is noteworthy that patients with stress-related disorders exhibit increased vulnerability to mental illness, even years after the stress experience, which is able to generate long-term changes in the brain's architecture and function. High levels of glucocorticoids produced by the adrenal cortex of the stressed subject reduce neurogenesis, which contributes to the development of depression. In support of the brain–adrenal connection in stress, many (but not all) depressed patients have alterations in the components of the limbic-hypothalamic-pituitary-adrenal (LHPA) axis, with enlarged adrenal cortex and increased glucocorticoid levels. Other psychiatric disorders, such as post-traumatic stress disorder, bipolar disorder and depression, are also associated with abnormalities in hippocampal volume and hippocampal function. In addition, hippocampal lesions impair the regulation of the LHPA axis in stress response. Our knowledge of the functional connection between stress, brain function and adrenal has been further expanded by two recent, independent papers that elucidate the effects of stress on brain and adrenal stem cells, showing similarities in the way that the progenitor populations of these organs behave under stress, and shedding more light into the potential cellular and molecular mechanisms involved in the adaptation of tissues to stress.